1998
DOI: 10.3354/meps174159
|View full text |Cite
|
Sign up to set email alerts
|

Soft-sediment benthic community structure in a coral reef lagoon ‹ the prominence of spatial heterogeneity and Œspot endemism¹

Abstract: ABSTRACT. An encompassing view of coral reef ecosystems needs to extend beyond the prominent and attractive hard substrata to include soft-sediment habitats associated with the reefs. Focusing on the soft-sediment assemblages withm the lagoon of the Great Astrolabe Reef (Fiji), we quantified patterns, clines and variability of community structure across space and evaluated models for marine biodiversity conservation based on the spatial distribution and ranty of benthic species Water depth sampled ranged from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
2
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 40 publications
6
55
2
5
Order By: Relevance
“…When the conservation target includes representation of all species and assemblage types, and turnover in both variables is high, the areas required will be large. In the present study 92% of locations were required to achieve the representation target of all species and assemblage types being represented and, in spite of differences in biotic group, spatial scale, sampling methodology, and environment, this result is similar to area requirements found in other studies for the same target (Schlacher et al, 1998;Ward et al, 1999;Gladstone, 2002;Beger et al, 2003). Significant areas of coastline will still be required to implement more modest conservation targets.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…When the conservation target includes representation of all species and assemblage types, and turnover in both variables is high, the areas required will be large. In the present study 92% of locations were required to achieve the representation target of all species and assemblage types being represented and, in spite of differences in biotic group, spatial scale, sampling methodology, and environment, this result is similar to area requirements found in other studies for the same target (Schlacher et al, 1998;Ward et al, 1999;Gladstone, 2002;Beger et al, 2003). Significant areas of coastline will still be required to implement more modest conservation targets.…”
Section: Discussionsupporting
confidence: 74%
“…A greater sampling effort may expand the range of species already discovered (thereby reducing the total number of unique species). However, it is also likely to discover additional unique species (see also Schlacher and Wooldridge (1996) and Schlacher et al (1998) for similar findings). The point at which additional sampling fails to find additional species and unique species is likely to be beyond the scope of fieldwork, given the depth of this habitat and practical considerations of dive duration.…”
Section: Discussionmentioning
confidence: 99%
“…Ellingsen (2001) showed that sites of high species richness were those rich in restricted-range species. This does not always hold true in marine systems (Schlacher et al 1998), and in the present study local species richness was only weakly related to the number of uniques. The selection of a limited number of species-rich areas will therefore not guarantee effective conservation of restricted-range species, because a large proportion of them may occur outside the species-rich areas.…”
Section: Distributions Of Speciescontrasting
confidence: 77%
“…Although many small invertebrates can inhabit the soft-bottoms around reefs, few research projects have investigated the community ecology of the macrofauna in reef complexes. In fact, the majority of the studies focus only on corals and fishes (SCHLACHER et al, 1998;HUGHES et al, 2002;LEÃO, 2002;BAILEY-BROCK et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1980s, when ecological studies of the macrofauna of reef complexes started, the main aim has been to investigate the influence of distance from the reef on the community concerned (RIDDLE et al, 1990;SCHLACHER et al, 1998;NETTO et al, 1999a;NETTO et al, 1999b;LANGLOIS et al, 2005;LANGLOIS et al, 2006). However, it is very difficult to compare these studies since they were conducted on different types of reef (coral reefs, rocky reefs or artificial reefs), different reef habitats (pools, lagoons or the sublittoral zone around the reefs) and on different distance scales (from few meters to few kilometers).…”
Section: Introductionmentioning
confidence: 99%